which example correctly demonstrates polynomial addition

(2x^2+6x+1)+(3x^2+3x+9)=-x^2+3x-8
(2x^2+6x+1)+(3x^2+3x+9)=5x^2+9x+10
(2x^2+6x+1)+(3x^2+3x+9)=13x^2+9x+10
(2x^2+6x+1)+(3x^2+3x+9)=5x^4+9x^2+10

1 answer

To determine which example correctly demonstrates polynomial addition, we need to add the polynomials \(2x^2 + 6x + 1\) and \(3x^2 + 3x + 9\):

  1. Add the coefficients of \(x^2\):

    • \(2 + 3 = 5\)
  2. Add the coefficients of \(x\):

    • \(6 + 3 = 9\)
  3. Add the constant terms:

    • \(1 + 9 = 10\)

Combining all these results, we get: \[ (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 \]

Thus, the correct example that demonstrates polynomial addition is: \[ (2x^2+6x+1)+(3x^2+3x+9)=5x^2+9x+10 \]

Similar Questions
  1. Which example correctly demonstrates polynomial addition?A, (2x^2+6x+1) + (3x^2+3x+9)=-x^2+3x-8 B, (2x^2+6x+1) + (3x^2+3x+9)=
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Which example correctly demonstrates polynomial addition?A. (2x^2 + 6x + 1) + (3x^2 + 3x + 9) = 5x^2 + 9x + 10 B. (2x^2 + 6x +
    1. answers icon 1 answer
  3. Which example correctly demonstrates polynomial addition?A. (2x^2+6x+1) + (3x^2+3x+9)=-x^2+3x-8 B. (2x^2+6x+1) + (3x^2+3x+9)=
    1. answers icon 1 answer
more similar questions